Artificial wetlands as alternative habitat for a wide range of waterbird species. (May 2022) - Rajpar, Muhammad Nawaz; Ahmad, Shahid; Zakaria, Muhammad; Ahmad, Adnan; Guo, Xinle; Nabi, Ghulam; Wanghe, Kunyuan
Highlights: Anthropogenic activities have deteriorated wetlands and the biodiversity within. Artificial wetlands can serve as an alternative habitat for waterbird communities. Establishing artificial wetlands can help in conserving waterbird communities. Abstract: Natural wetlands are at the cutting edge of protection concerns, as they harbor a greater range of waterbird assemblages than artificial wetlands. However, more than 50.0% of natural wetland areas and more than 17.0% of waterbird species have become imperiled due to human activities over the last two decades. Thus, it is important to understand whether artificial wetlands play significant roles as alternative habitats for wetland birds. The distance sampling point count method was employed to ascertain the difference in waterbird assemblages inhabiting Lungh natural wetland and Raja artificial wetland in Sindh Province, Pakistan from September 2017 to February 2019. Natural wetlands harbored 39, 282 individuals representing 40 waterbird species and 14 families, while artificial wetlands hosted 23, 122 individuals representing 39 species and 13 families. In total, 37 species were identified as least concern, 3 were near threatened, and one species was endangered, one vulnerable, and one data deficient. Anas crecca (4.95%) and A. platyrhynchos (4.72%) were the foremost abundant species in natural wetlands. A. crecca (4.57%) and A. clypeata (3.95%) were the foremost prevailing species of artificial wetlands. Alcedo atthis, Charadrius leschenaultia, and Vanellus leucurus did not utilize natural wetlands, while Bubulcus ibis, Larus genei, Tringa brevipes, and Plegadis falcinellus avoided artificial wetlands. The relative abundance of waterbirds between natural and artificial wetlands varied considerably (F1, 85 = 6.26, p < 0.05). Diversity indices indicated that natural wetlands attracted a greater diversity of waterbirds than artificial wetlands. The results indicated that natural wetlands had attracted a larger number of migrating birds than artificial wetlands. In contrast, artificial wetlands harbored a wide range of resident waterbird species than natural wetlands. As a result, we accept the hypothesis that artificial wetlands may serve as an alternative habitat for a wide range of waterbird communities. Hence, it is strongly recommended that artificial wetlands be constructed to harbor a wider array of waterbird species to halt wetland habitats and biodiversity loss across the country.